2021
DOI: 10.21203/rs.3.rs-159617/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of the SA-Associated Plant Defense Pathway Alters the Composition of Soil Bacterial Communities

Abstract: Background and aimsMany plant species grow better in sterilized than in live soil. Foliar application of SA mitigates this negative effect of live soil on the growth of the plant Jacobaea vulgaris. To examine what causes the positive effect of SA application on plant growth in live soils, we analyzed the effects of SA application on the composition of active rhizosphere bacteria in the live soil. Methods We studied this over four consecutive plant cycles (generations), using mRNA sequencing of the microbial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous studies showed that inoculation of a sterilized soil with natural, live soil reduced plant growth in comparison with that in sterilized soil for the plant species Jacobaea vulgaris (Joosten et al 2009;Kos et al 2015). Interestingly, applying SA to the leaves mitigated these negative effects (Jing et al 2021). This implies that activation of SAinduced resistance may potentially suppress microbial pathogens present in live soil.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies showed that inoculation of a sterilized soil with natural, live soil reduced plant growth in comparison with that in sterilized soil for the plant species Jacobaea vulgaris (Joosten et al 2009;Kos et al 2015). Interestingly, applying SA to the leaves mitigated these negative effects (Jing et al 2021). This implies that activation of SAinduced resistance may potentially suppress microbial pathogens present in live soil.…”
Section: Introductionmentioning
confidence: 94%
“…The current study focused on the effect of foliar SA application on the composition of the bacterial community in the rhizosphere in the inoculated soil. The effects of foliar application of SA on plant growth in the four generations were described elsewhere (Jing et al 2021). A summary of the effects of foliar SA application on the growth of J. vulgaris are shown in Fig.…”
Section: Multi-generational Plant Growth Experimentsmentioning
confidence: 99%